Keefektifan Permainan Susun Kata Untuk Penguasaan Partikel Bahasa Jepang Pada Siswa Kelas XI MAN 2 Pekanbaru - Winda, Winda; Nimashita, Hana; Utami, Mutiara Rahmi (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2025)
The use of Japanese particles remains a challenge for students, as they often struggle to distinguish particle functions, determine their correct positions within sentences, and maintain focus during learning activities. Therefore, a word arrangement game was implemented in the learning process. This study aims to examine the effectiveness of the word arrangement game in improving students’ mastery of basic Japanese particles. The research employed a quantitative approach with a quasi-experimental pretest–posttest control group design involving 62 eleventh-grade students of MAN 2 Pekanbaru, divided into experimental and control classes. The research instruments consisted of pretest and posttest items totaling 30 questions, analyzed using the Shapiro–Wilk normality test, homogeneity test, independent t-test, and Mann–Whitney U test. The results showed that the experimental class obtained a higher posttest mean score (72.19) than the control class (56.77), with a significance value of 0.001 (<0.05). Thus, it can be concluded that the word arrangement game is effective in enhancing students’ mastery of Japanese particles, although their overall achievement remains in the low category. The particles most frequently used in students’ constructed sentences were wa, o, no, and de.